SUSTAINABLE URBAN DRAINAGE DESIGN IN BOR COUNTY-SOUTH SUDAN - Ngong Deng, Abraham Ayuen; Hapsari, Ratih Indri; Harsanti, Winda (Jurusan Teknik Sipil Politeknik Negeri Malang, 2023)
Urbanization and an increase in the population in Bor County put pressure on the environment as more land is exploited and existing urban areas are further developed and densified which already put high pressure to handle the risks of climate change. Urban drainages system should be designed to create more resilience to floods for sustainable areas, where flood management is one of the challenges that need to be tackled. This research formulation aims to answer some of the key factors regarding designing a sustainable urban drainage system as a means of reducing the risks of flooding, improving water quality, and promoting sustainable development. The type of drainage used is the open channel type and includes the non-level series with parts including the main channel, sub-channel dimensions, and infiltration wells. To be able to achieve a sustainable and resilient urban drainage system, we have to handle the volume of runoff water with rainfall data for 10 years which is important for the flooding implementation process which changes reputably each year. It is crucial to design and implement facilities and systems that are sustainable, and multifunctional for designing SUDS in Bor with hydraulic and hydrology methods. The implementation process needs to use cost estimation approaches that include flood mitigation and co-benefits, in the long-term and short-term simultaneously. From the results, the design of rain is 73.82 mm/day for 2 years return period, and 93.08 mm/day for 5 years return period. The data is then used as the basis for planning the channel dimensions with several channels of the urban drainage system. The results are in the form of a total main dimension height of 5 meters, total width of 3.52 meters, and a length of 76 meters with the security control of soil stability to carry a capacity of 5m3/s. The budget plan for total cost estimation is IDR 15.511.693.828.